Effect of Red Dragon Fruit Extract (Hylocereus polyrhizus) on Total Cholesterol Levels in Wistar Rats Model of Metabolic Syndrome - Apriliani, Devina; Subandono, Jarot; Budiastuti, Veronika Ika; Hermawan, Danus (Smart Medical Journal, 2024)
Introduction: The consumption of high fat and sugar can increase the risk of metabolic syndrome. Hylocereus polyrhizus is known to be able to lower total cholesterol levels in the blood. This study aims to determine the effect of Hylocereus polyrhizus extract on total cholesterol levels in Wistar rats with the metabolic syndrome model.Methods: This study used laboratory experimental research using a pretest and posttest with a control group design. The sample consisted of 30 Wistar rats according to the inclusion criteria which were divided into 5 groups: K1 (positive control), K2 (negative control), K3, K4, and K5 (treatment group). The treatment group was given Hylocereus polyrhizus extract with doses of 60, 120, and 180 mg/200grW. Total cholesterol levels were measured on the 8th, 36th, and 64th day. The data were analyzed using the parameterized One-way ANOVA test followed by Tukey's HSD posthoc test, paired T-test, and Pearson's correlation test.Results: The average total cholesterol after being given by Hylocereus polyrhizus extract in K3 (137 ± 2.82 mg/dL), K4 (109 ± 2.31 mg/dL), and K5 (100 ± 2.38 mg/dL) was lower than the negative control group. Data analysis showed significant differences (p<0.05) in total cholesterol levels before and after treatment in all groups. The Pearson correlation test explained that the variation dosage of Hylocereus polyrhizus extract had a very strong correlation with a positive correlation with total cholesterol levels.Conclusion: Induction of Hylocereus polyrhizus extract at doses of 60, 120, and 180 mg/200grW was able to significantly reduce total cholesterol levels.